Cervicothoracic Thymic Cyst: An Unusual Presentation - Rajakumar, Anjith Prakash (Korean J Thorac Cardiovasc Surg, 2018)
Cervicothoracic thymic cysts are rare and difficult to diagnose preoperatively. We report a case of a cervicothoracic thymic cyst presenting as a lateral neck mass and mimicking a laryngocele in a 3-year-old boy and its definitive management.